Pharmacology of Bradykinin-Evoked Coughing in Guinea Pigs - Hewitt, Matthew M. (J Pharmacol Exp Ther, 2016)
Bradykinin has been implicated as a mediator of the acute pathophysiological and inflammatory consequences of respiratory tract infections and in exacerbations of chronic diseases such as asthma. Bradykinin may also be a trigger for the coughing associated with these and other conditions. We have thus set out to evaluate the pharmacology of bradykinin-evoked coughing in guinea pigs. When inhaled, bradykinin induced paroxysmal coughing that was abolished by the bradykinin B(2) receptor antagonist HOE 140. These cough responses rapidly desensitized, consistent with reports of B(2) receptor desensitization. Bradykinin-evoked cough was potentiated by inhibition of both neutral endopeptidase and angiotensin-converting enzyme (with thiorphan and captopril, respectively), but was largely unaffected by muscarinic or thromboxane receptor blockade (atropine and ICI 192605), cyclooxygenase, or nitric oxide synthase inhibition (meclofenamic acid and N(G)-nitro-L-arginine). Calcium influx studies in bronchopulmonary vagal afferent neurons dissociated from vagal sensory ganglia indicated that the tachykinin-containing C-fibers arising from the jugular ganglia mediate bradykinin-evoked coughing. Also implicating the jugular C-fibers was the observation that simultaneous blockade of neurokinin(2) (NK(2); SR48968) and NK(3) (SR142801 or SB223412) receptors nearly abolished the bradykinin-evoked cough responses. The data suggest that bradykinin induces coughing in guinea pigs by activating B(2) receptors on bronchopulmonary C-fibers. We speculate that therapeutics targeting the actions of bradykinin may prove useful in the treatment of cough.